Need Assessment for Developing Learning Modules Based on Discovery Learning Ecosystem Materials - Geni, Rangga; Sumah, Astrid Sri Wahyuni (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The scientific approach is a form of character education integrated into learning activities. The success of implementing character values internalization learning is largely determined by the teacher's skills in selecting and implementing appropriate learning models. However, in reality, school teachers still do not apply learning models that suit the students' character, and the teaching materials used also do not support character internalization learning. So, this research aims to determine the characteristics of students and the type of materials and modules to be developed based on conditions in the field. This research uses qualitative research with a descriptive approach based on ongoing problems in class X SMA Bina Ilmi, Palembang City—techniques for obtaining data in the field, namely interview techniques, observation, and documentation. The research results showed that students were of an age that had entered the formal operational stage, understood abstract concepts, had high curiosity, and tended to like discovering new things. Meanwhile, the material analysis results showed three ecosystem materials that can stimulate students' curiosity: interactions between species, ecosystem components, and ecological pyramids. This material will be made into a teaching module based on discovery learning. This model-based module can make students build their knowledge through independent observation to increase students' reasoning power in developing environmental concepts following ecosystem material and learning resources that can provide interesting discovery concepts to explore curiosity to observe and process information in the learning process and understand ecosystem material.